If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(2x + 5) = 0 Reorder the terms: 3x + -1(5 + 2x) = 0 3x + (5 * -1 + 2x * -1) = 0 3x + (-5 + -2x) = 0 Reorder the terms: -5 + 3x + -2x = 0 Combine like terms: 3x + -2x = 1x -5 + 1x = 0 Solving -5 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = 0 + 5 1x = 0 + 5 Combine like terms: 0 + 5 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| -4(1+r)=32 | | 2*6=12x | | -4(-2+x)=-16 | | -4(-2+x)=-6 | | -77=-7x | | 180-x=14*x | | 8x^2+21x-12=0 | | F(3)-9=5n+4n | | 180-x=19*x | | -7=a-6 | | 3+3(x+6)-45+6-8/2+3=27 | | 3+3(x+6)-4*5+6-8/2+3=27 | | 50+7x-8x+3x=-10 | | -19=v-15 | | 180-x=19(90-x) | | 26-4x+12+6x=-16 | | 180-x=14(90-x) | | 40+2x-3x+5x=40 | | 40x+2x-3x+5x=40 | | -5(4b+4)+(21b-3)=0 | | (13b-9)-3(4b+4)=-5 | | 5+2*5= | | -3x+15=-10+10 | | 45-9x=5x-25 | | 5+2*-5= | | 3*-5=5+2*-5 | | 3b+-1=5 | | 9x-6x=27 | | 2(x+8)-3=4(x-6) | | -7/10=4/3 | | -4p=8/3 | | (3x-1)(3x-1)=12 |